2016
DOI: 10.1016/j.electacta.2016.08.108
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Reactions Coupled with Chemical Reactions of Oxygen, Water and Acetaldehyde in an Ionic Liquid: New Approaches for Sensing Volatile Organic Compounds

Abstract: Water and oxygen are ubiquitous present in ambient conditions. This work studies the unique oxygen, trace water and a volatile organic compound (VOC) acetaldehyde redox chemistry in a hydrophobic and aprotic ionic liquid (IL), 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide ([Bmpy] [NTf2]) by cyclic voltammetry and potential step methods. One electron oxygen reduction leads to superoxide radical formation in the IL. Trace water in the IL acts as a protic species that reacts with the superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Angell and Dickinson have determined ∂ α /∂E values for the Fe 3+ /Fe 2+ and Fe(CN) 6 3− / Fe(CN) 6 4− systems in aqueous solutions at platinum and gold electrodes. Similar results one can find in papers published in 2011 and later where the same elements occur together: repeated independent scans, adsorption layer on or modification of solid electrode, and isopoints. Therefore, the experimental facts presented there can be interpreted as iap occurrence.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Angell and Dickinson have determined ∂ α /∂E values for the Fe 3+ /Fe 2+ and Fe(CN) 6 3− / Fe(CN) 6 4− systems in aqueous solutions at platinum and gold electrodes. Similar results one can find in papers published in 2011 and later where the same elements occur together: repeated independent scans, adsorption layer on or modification of solid electrode, and isopoints. Therefore, the experimental facts presented there can be interpreted as iap occurrence.…”
Section: Resultssupporting
confidence: 62%
“…The occurrence of intersection points (isopoints) for ordered sets of current‐potential responses was described and discussed by several authors , and the problem is still present in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that in aqueous solvent, hydrogen oxidation involves two oxidation steps, the first step is the formation of hydrogen adsorbate on platinum (Pt–H ad ) also known as the Tafel step, and the second step is dissociative oxidation step (typically referred as Heyrovsky and Volmer step) . However, it is also found that electrolytes can play a significant role in altering the reaction pathway of HOR. , For example, ionic liquids (ILs) composed of organic cations or anions are widely employed as nonaqueous electrolytes in various chemical and electrochemical applications including fuel cells and batteries. , Our previous investigation shows that the oxidation of hydrogen in ILs at an aerobic condition utilizes a different reaction pathway that involves the coupling reaction with oxygen . Walsh et al also found an inhibition effect of HOR in protic ionic liquids due to the formation of adsorbed oxide layer on platinum surface .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For example, ionic liquids (ILs) composed of organic cations or anions are widely employed as nonaqueous electrolytes in various chemical and electrochemical applications including fuel cells and batteries. 8,9 Our previous investigation shows that the oxidation of hydrogen in ILs at an aerobic condition utilizes a different reaction pathway that involves the coupling reaction with oxygen. 10 Walsh et al also found an inhibition effect of HOR in protic ionic liquids due to the formation of adsorbed oxide layer on platinum surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the various Clark-cell type designs, some highlights include the detection of oxygen [22,23,25] and hydrogen [24,26] gases. Figure 2 shows a schematic of a sensor device used for detecting hydrogen gas with fast response times; hydrogen flows into the cell, where it diffuses through a gas-permeable membrane to the sensing electrode and is oxidised.…”
Section: Porous Working Electrodes Based On the Conventional Clark-cell Designmentioning
confidence: 99%